Unusual presentation of a curve-shaped Meckel's diverticulum detected on technetium-99m Meckel's scintigraphy - Anitha, Dharmalingam; Shwetal, Pawar; Suruchi, Shetye; Mangala, Ghorpade (World Journal of Nuclear Medicine, 2020)
Complicated Meckel's diverticulum (MD) in pediatric age group may not present with classic symptoms or signs. The routine modalities of investigations for the detection of MD are ultrasonography (US), computerized tomography, and air enema. However, these may miss the diagnosis in cases of atypical patterns of presentation. In such situations, the radionuclide Meckel scan helps to narrow down the diagnosis. The objective of this case report was to present an unusual presentation of MD where the diagnosis was established by a radionuclide scan against other methods which were equivocal. An 8-year-old boy was admitted with features of intestinal obstruction.99mTc-pertechnetate Meckel's scintigraphy showed localization of tracer in ectopic gastric mucosa. The surgical exploration after the Meckel's scan revealed a curve-shaped MD localized 50 cm proximal to the ileocecal valve. The surgery was completed after a diverticulectomy, and the patient was relived of symptoms. MD scintigraphy can help detect ectopic gastric mucosa in cases of unusual presentation by considering the atypical presentation, variation in shape, and location on Meckel's scan and improve the disease management.
Keywords: Gastric mucosa; meckel's diverticulum; radionuclide Meckel's scan